2020
DOI: 10.1186/s13075-020-2104-7
|View full text |Cite
|
Sign up to set email alerts
|

Self-reactive T cells induce and perpetuate chronic relapsing arthritis

Abstract: Background: CD4 + T cells play a central role during the early stages of rheumatoid arthritis (RA), but to which extent they are required for the perpetuation of the disease is still not fully understood. The aim of the current study was to obtain conclusive evidence that T cells drive chronic relapsing arthritis. Methods: We used the rat pristane-induced arthritis model, which accurately portrays the chronic relapsingremitting disease course of RA, to examine the contribution of T cells to chronic arthritis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Phytol interacts with the nuclear factor kappa -B (NF-κB) signaling pathway and migration of neutrophils into inflammation sites that further causes the inhibition of pro-inflammatory cytokines such as TNF-α and interleukin -6, hence can regulate the inflammatory process of arthritis 25,28 .…”
Section: Resultsmentioning
confidence: 99%
“…Phytol interacts with the nuclear factor kappa -B (NF-κB) signaling pathway and migration of neutrophils into inflammation sites that further causes the inhibition of pro-inflammatory cytokines such as TNF-α and interleukin -6, hence can regulate the inflammatory process of arthritis 25,28 .…”
Section: Resultsmentioning
confidence: 99%
“…In vitro and in vivo studies have demonstrated that presentation of peripheral tissue self-antigens is quantitatively determined by AIRE transcription, and AIRE SNPs may cause clonal survival (19,47). Autoreactive CD4 + T cells are recruited to the synovium where they initiate an inflammatory environment by the production of interferon-gamma, tumor necrosis factor-alpha, interleukins (ILs), proinflammatory cytokines, and chemokines, causing tissue destruction (48)(49)(50). The inflammatory environment activates fibroblast-like synoviocytes (FLSs) to produce chemokines in order to attract more autoreactive CD4+ T cells, creating a vicious circle (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, from an immunogenetics standpoint, T-lymphocyte pathways play a significant role in inducing and perpetuating chronic relapsing arthritis of D2TRA[ 12 ]. Cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) was first identified as an inhibitory signal that is delivered to stop the immune response and has the potential to adversely limit T-lymphocyte activation in various ways[ 13 ]. In several research investigations, the prevalence of D2T RA ranged from 5% to 20% of patients with RA[ 14 ].…”
Section: Discussionmentioning
confidence: 99%